From celluloid to cyberspace : the media arts and the changing arts world - McCarthy, Kevin F., 1945- (Rand, 2002)
The arts in America are entering a new era that will pose many challenges for the arts community. However, our current knowledge of the operation of the arts world and its underlying dynamics is limited. These limits are particularly pronounced with regard to the newest and most dynamic component of the arts world: the media arts. Defined as art that is produced using or combining film, video, and computers, the media arts encompass a diverse array of artistic work that includes narrative, documentary, and experimental films; videos and digital products; and installation art using media. This.